2014
DOI: 10.1007/s00376-014-0008-7
|View full text |Cite
|
Sign up to set email alerts
|

From MONEX to the global monsoon: A review of monsoon system research

Abstract: Substantial progress has been made over the past three decades since the Monsoon Experiments (MONEX) of 1978-79. Here, we review these achievements by highlighting four breakthroughs in monsoon research: (1) The identification of the coupled ocean-land-atmosphere nature of the monsoon in the process of the annual cycle of solar heating; (2) new understanding of the changes in the driving forces of monsoon systems, with anthropogenic factors (climate effects of increased greenhouse gas and aerosol emissions) pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
31
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(32 citation statements)
references
References 93 publications
0
31
0
Order By: Relevance
“…Land masses heat up more prominently than the surrounding ocean during summer in East Asia due to a faster response to the seasonal cycle in solar heating, thus forming a large temperature gradient that can drive wind blowing from the ocean toward the land (Webster and Yang 1992;Ding et al 2015). The EASM is the most important climate system in East Asia, and changes in this system have significant effects on East Asian weather and climate (Ding and Chan 2005;Ding et al 2008;Lei et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Land masses heat up more prominently than the surrounding ocean during summer in East Asia due to a faster response to the seasonal cycle in solar heating, thus forming a large temperature gradient that can drive wind blowing from the ocean toward the land (Webster and Yang 1992;Ding et al 2015). The EASM is the most important climate system in East Asia, and changes in this system have significant effects on East Asian weather and climate (Ding and Chan 2005;Ding et al 2008;Lei et al 2011).…”
Section: Introductionmentioning
confidence: 99%
“…The precipitation associated with the monsoonal circulation is critical for the social and economic well‐being of billions of people. As such, monsoons have been an active research subject for over half a century, especially since the Monsoon Experiment of 1978–1979 during the First Global Atmosphere Research Plan Global Experiment where the majority of studies focused on the Asian monsoon (AM) system [ Ding et al ., ].…”
Section: Introductionmentioning
confidence: 99%
“…The monsoon has also varied with glacial-interglacial cycles and on geological time scales, and now future changes in the monsoon system under anthropogenic influences are of great concern. Accumulated observational and paleo-proxy data, field experiments and numerical studies have revealed various aspects of the monsoon and its variability (Webster et al 1998;Chang et al 2011;Ding et al 2015). This article focuses on the seasonal mean monsoon and its future changes as simulated and projected by climate models.…”
Section: Introductionmentioning
confidence: 99%